2018
DOI: 10.1016/j.adro.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of radiation-induced acute skin toxicity in breast cancer at a single institution: Role of fractionation and treatment volume

Abstract: PurposeThe associations among radiation fractionation, body mass index (BMI), and acute skin toxicity with adjuvant radiation for breast cancer is of increasing interest. This study evaluated the rate of grade ≥2 dermatitis and moist desquamation (MD) in patients with a high BMI who were treated to the breast or chest wall to understand the role of radiation target, fractionation regimen, and BMI.Methods and materialsWe retrospectively evaluated 280 patients treated with adjuvant radiation for breast cancer af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 17 publications
2
29
1
Order By: Relevance
“…We had no grade 4 or 5 events. A recent retrospective analysis of breast cancer patients treated with radiation after surgery showed that acute skin toxicity was associated with elevated BMI and regional nodal irradiation . Likewise, we found that BMI > 30 kg/m 2 was associated with the development of severe toxicity.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…We had no grade 4 or 5 events. A recent retrospective analysis of breast cancer patients treated with radiation after surgery showed that acute skin toxicity was associated with elevated BMI and regional nodal irradiation . Likewise, we found that BMI > 30 kg/m 2 was associated with the development of severe toxicity.…”
Section: Discussionsupporting
confidence: 61%
“…A recent retrospective analysis of breast cancer patients treated with radiation after surgery showed that acute skin toxicity was associated with elevated BMI and regional nodal irradiation. 49 reRT, and 10% had concurrent chemotherapy with reRT. Inoperable localized disease can cause significant morbidity and have high rates of toxicities when treated with radiation and concurrent chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The lower skin dose in the MCoptimized plans could then translate into a lower likelihood of severe radiation dermatitis. Previous studies by Liang et al 18 and by Parekh et al 19 showed that the risk of moist desquamation is much higher in post-mastectomy radiation therapy compared with breast conservation settings. Our current study also compared intact breast and CW groups.…”
Section: Discussionmentioning
confidence: 98%
“…The only factor associated with grade 3 RD in our study was BMI (P = .02), which is consistent with other studies. 15,16 However, it is unclear if this is due to increased skin folds, larger amount of skin irradiated, or other factors. Furthermore, most patients in our study were treated with conventional fractionation.…”
Section: Discussionmentioning
confidence: 99%